2018
DOI: 10.3762/bjnano.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Review on optofluidic microreactors for artificial photosynthesis

Abstract: Artificial photosynthesis (APS) mimics natural photosynthesis (NPS) to store solar energy in chemical compounds for applications such as water splitting, CO2 fixation and coenzyme regeneration. NPS is naturally an optofluidic system since the cells (typical size 10 to 100 µm) of green plants, algae, and cyanobacteria enable light capture, biochemical and enzymatic reactions and the related material transport in a microscale, aqueous environment. The long history of evolution has equipped NPS with the remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 122 publications
0
21
0
Order By: Relevance
“…The substrate of photoelectrode is responsible for the growth of semiconductor materials and transfer of electrons in the external circuit. The related half-reaction equations on two electrodes are shown in Equations (2) and (3). The photoelectrodes work as a sunlight absorber, capturing solar energy to driving water splitting.…”
Section: Pec Water Splitting Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The substrate of photoelectrode is responsible for the growth of semiconductor materials and transfer of electrons in the external circuit. The related half-reaction equations on two electrodes are shown in Equations (2) and (3). The photoelectrodes work as a sunlight absorber, capturing solar energy to driving water splitting.…”
Section: Pec Water Splitting Processmentioning
confidence: 99%
“…[1][2][3][4][5] It is said that the existence of environmental issues partly attributes to the unreasonable use of traditional fossil fuel, such as excessive exploitation and inefficient utilization. Therefore, effective solutions should be proposed to address these issues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optofluidic reactors have intrinsic merits, such as fine flow control, large surface-to-volume ratio, and direct delivery of light to the reaction surface, making them natural photoreactors for photocatalysis [7][8][9][10]. Some studies showed microfluidic methods for achieving good degradation efficiency of polluted water [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…They inherit many advantages from microfluidics technology, such as small dimensions, high surface-to-volume (S/V) ratio, easy control of flow rates, short molecular diffusion distance, rapid reaction speed, high reaction efficiency, low reagent consumption, fast heat dissipation, uniform illumination of light, as well as potential portability and disposability [2,16,[21][22][23]. Although a single microreactor has very limited output (~1-100 L/h), the throughput can be scaled up by connecting many devices in parallel, sizing up the reactor dimensions, and even stacking multiple layers of the same devices [14,[24][25][26].Based on the above considerations, this work will incorporate the plasmonic effect into the microreactors so as to exert the full power of both for the enhancement of photodegradation efficiency. The microreactor is bonded on an FTO glass substrate to have a planar reaction chamber, the bottom part of which is decorated by gold nanoparticles (AuNPs) and then covered by a thin TiO 2 layer (Figures 1 and 2).…”
mentioning
confidence: 99%